THE ECONOMIC CONVERGENCE IN THE EUROPEAN MODEL - CISMAS Laura; SIRGHI Nicoleta (Annals of the University of Oradea: Economic Science, 2009)
The economic convergence consists in the very close, even identical evolutions of one variable in two different countries or regions. Within the European model, the macroeconomic and cohesion policies insure a good substantiation of the sustained economic